Pelatihan Ecoprint Pada Totebag Dalam Meningkatkan Kreatifitas Anak di desa Pasinan Kecamatan Lekok Pasuruan - Ishtifaiyyatul Qudsi; Nunik Hidayati; Farihah Ainun; Rahayu Mardikaningsih; Didit Darmawan; Mila Hariani; Rommy Hardyansah (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2024)
"Eco" (ecosystem) means nature, and "Print" means printing. These two words are combined into the word ecoprint. This method was developed with the aim of producing high-quality artwork using natural materials as dyes and design motifs. Leather is one of the materials used to make the ecoprint process. Namely leaves and plant flowers. Although each fabric uses the same type of plant leaves, the ecoprint process uses natural materials to create unique themes and patterns on each fabric. Using the PAR (Participatory Action Research) service method in the form of an approach by increasing community participation so that they can participate in the activity. This activity begins by determining the right day and date of implementation after that conducting observations and permission from the principal at MI Ihatta and MI Miftahul Ulum schools to be able to carry out activities at the school, in addition, ecoprint training activities are also held in the yard of the village hall office. There are several ways to make ecoprints, including (1) turning the tote bag inside out, (2) lining the inside with plastic so that the resulting color does not spread, (3) arranging several plant shapes on the tote bag and using the leaves and flowers, (4) after that cover the arranged plant parts using other plastic, (5) hit it using a stone or hammer slowly while holding the plastic cover so that the results obtained are not messy, (6) and the last stage is removing the remains of the plants that are stuck to the tote bag, after that turning the tote bag back to its original position and forming several beautiful motifs from the plant parts.